The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1111/j.1651-2227.1996.tb13927.x
|View full text |Cite
|
Sign up to set email alerts
|

Pubertal stages 1980 of Stockholm schoolchildren

Abstract: In March 1980 a cross-sectional study of the pubertal developmental of a sample of Stockholm schoolchildren was conducted. Breast development (B1-B5), pubic hair (PH1-PH5) and axillary hair (AH1-AH3) were rated in 138 girls, and genitalia development (G1-G5), pubic hair (PH1-PH5) and axillary hair (AH1-AH3) were rated in 116 boys according to the Tanner method. The girls' and the boys' ratings were done by one female and one male medically qualified expert respectively. When relating social class to age of pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 1 publication
5
37
1
1
Order By: Relevance
“…Other studies that found no relationship involved well-off populations without threats to maturation from nutritional stress. 51,52 The Akwesasne Mohawk sample demonstrates no evidence of nutritional deficiency that would affect menarche, 53,54 and the observed relationship between menarche and SES fits the pattern observed for welloff samples.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Other studies that found no relationship involved well-off populations without threats to maturation from nutritional stress. 51,52 The Akwesasne Mohawk sample demonstrates no evidence of nutritional deficiency that would affect menarche, 53,54 and the observed relationship between menarche and SES fits the pattern observed for welloff samples.…”
Section: Discussionmentioning
confidence: 59%
“…Other studies that found no relationship involved well-off populations without threats to maturation from nutritional stress. 51,52 The Akwesasne Mohawk sample demonstrates no evidence of nutritional deficiency that would affect menarche, 53,54 and the observed relationship between menarche and SES fits the pattern observed for welloff samples.Here our focus was not on the relationship of SES to menarche but on the role of SES in influencing the relationship of lead and PCBs to menarche. In the present study, the removal of SES from the logistic regression model had little impact on the effects of age and toxicants on menarche (on the basis of changes in ␤ coefficients) or on the pseudo-variance explained (2.8% reduction in both Cox-Snell and Nagelkerke pseudo-R 2 ).…”
mentioning
confidence: 59%
“…Jahrhunderts auf etwa 12,5-13 Jahre eingependelt [18,19,20,21,22,23]. Dieser Trend in der Veränderung des Menarchealters wird durch Untersuchungen sowohl für Deutschland als auch für andere europäische Länder bestätigt [2,6,17,19,24,25,26,27]. Ergebnisse der 1985 in den jetzigen neuen Bundesländern durchgeführten repräsentativen Reifestudie an ca.…”
Section: Datenlageunclassified
“…Investigators have handled such missing data in a number of ways, either by substituting the mean age for girls with known ages, or using grade in school and presumed chronological age assuming the girl entered school at 5 years of age and did not skip or repeat a grade. Other crude proxies of pubertal development in girls include presence/absence of axillary hair (Lindgren 1996). Although there is no direct analogy of age at menarche for boys, there is a Tanner scale for assessing pubertal stage in boys.…”
Section: Tanner Scales: Anatomical Markers For Staging Pubertal Develmentioning
confidence: 99%